The Development of a Web Based UTHM Event Central Management System - EDI PUTRA, NORIL ATILA; DARMAN, ROZANAWATI (Applied Information Technology And Computer Science, 2025)
The UTHM Event Central project is designed to revolutionize the management and promotion of campus events at Universiti Tun Hussein Onn Malaysia by addressing significant challenges such as limited event visibility and fragmented communication channels. Utilizing the Agile methodology, this project introduces a centralized digital platform that enhances event visibility, simplifies the process of secretariat recruitment, and boosts student participation. Developed using HTML, CSS, PHP, JavaScript, Python, Flask and SQL, the platform incorporates user-centric functionalities like advanced search options, push notifications and interactive event listings, ensuring timely and relevant information is delivered to different user categories including students and university staff. Preliminary testing has demonstrated significant improvements in event visibility and management efficiency, with positive feedback from users indicating increased participation and satisfaction. Future work will focus on expanding the platform’s capabilities to include more personalized user interactions and broader integration with existing university systems, aiming to further enhance the effectiveness of event management at UTHM. This project not only streamlines the organization of events but also fosters a more vibrant and connected campus community.